Processes for producing virgin coconut oil, coconut cooking oil and raw material for coconut biodiesel - Khalid, Kaida; Nurdin, Rudy; Basri, Izzatul Hidayah; Che Man, Yaakob; Ramli, Irmawati (2008)
The present invention relates to an improved process for the preparation of virgin coconut oil (VCO), raw material for high quality coconut biodiesel and 5 coconut cooking oil from the coconut milk by applying microwave separation technology. It is based on the optimum set up of microwave power, time and temperature in the microwave irradiation separation system and initial preparation of coconut milk before microwave irradiation. Exposing the sample to microwave frequency at 2.45 GHz will rotate water molecules or dipoles at the rate of about 5 10 billions per second and free electrons and ions will oscillate or vibrate at the same rate. These effects will eventually create intermolecular collisions and will separate the sample into water, oil and solid. For preparation of VCO, the process is treated at the temperature less than 60?C while for raw material for coconut biodiesel and coconut cooking oil, the temperature is controlled up to 80?C. The whole process will take about 30 minutes at the power level of 15 about 500 Watt. Once the process was established, the oil can be separated using conventional methods such as gravitational separation or centrifuge method. A special treatment is applied for the preparation of VCO in order to reduce disturbances. Although the process temperature for VCO a little big higher than room temperature, the product retains the fresh scent and taste of coconuts. Furthermore, in terms of quality, this process can produce high quality VCO with 20 about 54% lauric acid and 8.1% capric acid which is much better than available commercial VCO. The coconut biodiesel which has been produced from this oil is saving a specific energy which is comparable to palm oil biodiesel. However, the solidification point for this coconut biodiesel is around -11?C, these makes it suitable for winter season. Generally, this new process is chemical free, a faster method, easy to operate, high yield of about 10-11 25 coconut per litre of biodiesel oil, good quality of VCO, coconut biodiesel and coconut cooking oil. Furthermore these processes are suitable for producing of virgin oil, cooking oil and raw material for biodiesel from a source obtained from fruits of jatropha or kenaf, palm fruitlet or palm kernel or similar fruits or seeds or oily based plant such as algae.